Adding 'something more' to looking: the interaction of artefact, verbiage and visitor in museum exhibitions. (February 2020) - Blunden, Jennifer
Around the world, museums dedicate enormous resources to developing exhibitions with the aim of making their collections and knowledge accessible to broad public audiences. Interpretive texts, both spoken and written, play an important role in this endeavour, underpinned by the belief that they will add 'something more' to the experience gained by looking alone. But is this belief justified? This article draws on recent theoretical developments in systemic functional linguistics (SFL) and multimodal semiotics to explore the complexity of meanings and relations involved in the interaction between (verbal) text, displayed artefact and visitor in an art exhibition and a history exhibition. Focusing on two key dimensions, vergence and presence, it shows how the texts work in very different ways to shape visitor experience, both in terms of scaffolding the interaction and in adding meaning to the encounter. It proposes the idea of 'verbal vectors' that are gradable in strength as a feature that explicitly 'motivates' visitors to look at the displayed artefacts and the idea of 'shell' vectors as a particular feature of texts in art exhibitions.